Seismic evaluation of steel plate shear wall systems considering soil-structure interaction. Issue 145 (June 2021) - Sarcheshmehpour, M.; Shabanlou, M.; Meghdadi, Z.; Estekanchi, H.E.; Mofid, M.
Abstract: This study investigates the various effects of Soil-Structure Interaction (SSI) on the seismic behavior of steel frames with Steel Plate Shear Wall (SPSW) lateral resisting systems. Nine steel frames with various aspect ratios are studied under multiple seismic hazard levels. The SPSWs are modeled based on the strip model concept, and the Soil-Structure Systems are simulated using the substructure method. The soil beneath the structure is considered as a homogeneous elastic half-space. The Endurance Time method is exploited for nonlinear dynamic analysis of the fixed-base structures and soil-structure systems. Results indicate that use of fixed-base models leads to the significant overestimation of the damage of SPSWs in the lower stories of the structure. Neglecting SSI in squat structures is undoubtedly a conservative choice, while in slender structures, it may lead to the underestimation of structural responses, especially in the upper stories. In the design procedure of the structures with SPSW lateral load resisting system located on soft soils, ignoring SSI effects results in very heavy and cost-intensive code-based designs. Highlights: Seismic evaluation of steel structures with SPSW system considering SSI effects using the endurance time method. For soft soils, first yielding of soil-structure systems occurs at hazard levels significantly more severe than design level. At high seismic intensities, use of fixed-base models leads to misprediction of structural responses and damaged locations. For structures with SPSWs located on soft soils, ignoring SSI effects results in very cost-intensive code-based designs.